Use of the active flipped classroom methodology in teaching transition metal complexes and their use in the production system - Mininel, Francisco José; Mininel, Silvana Márci Ximenes (Brazilian Journal of Production Engineering, 2026)
We present a methodological proposal for teaching chemistry based on the flipped classroom, aiming to overcome the traditional teaching model, which often demotivates students. We explore how this approach can be applied to promote greater student autonomy and active participation, using digital resources and collaborative activities. Aspects related to transition metal complexes and their applicability in the manufacturing sector were studied. Experience reports indicate that the methodology has the potential to optimize classroom time, deepen learning, and develop essential 21st-century skills, such as critical thinking and problem-solving.
Keywords: Flipped classroom; transition metal complexes; production sector